2023
DOI: 10.1037/pla0000186
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the PlayStrong Neuro-Filial Parenting Program: A program evaluation of an online pilot during COVID-19.

Abstract: This study piloted an online play-based parenting program informed by filial therapy, child-parent relationship therapy, and interpersonal neurobiology during COVID-19. The purpose of this program evaluation was to explore its potential effectiveness in improving child behaviors, mindful parenting, parent-child relationship quality, and protective factors. This study used a mixed method design to gather quantitative data from standardized measures and qualitative data from surveys. Parents of children 4-10 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…During COVID-19, two studies related to intervention-centric parenting activities utilising ICT were identified. Participation in online parenting interventions may result in improvements in three distinct areas (Tuntipuchitanon, 2022;Wisen-Vincent & Bokoch, 2022). First, online intervention programs, such as Triple-p/PPP, are associated with better social, emotional, and behavioural outcomes for children.…”
Section: Benefits Risks and Implicationsmentioning
confidence: 99%
See 4 more Smart Citations
“…During COVID-19, two studies related to intervention-centric parenting activities utilising ICT were identified. Participation in online parenting interventions may result in improvements in three distinct areas (Tuntipuchitanon, 2022;Wisen-Vincent & Bokoch, 2022). First, online intervention programs, such as Triple-p/PPP, are associated with better social, emotional, and behavioural outcomes for children.…”
Section: Benefits Risks and Implicationsmentioning
confidence: 99%
“…More importantly, rarely any feedback was given to parents during nor after their application of acquired strategies. Parents were not encouraged to ask questions or involved in discussion enough to involve deep insights, thus parents were less motivated compared with on-site participation (Wisen-Vincent & Bokoch, 2022). Therefore, there are two directions of implications emerging from the existing research.…”
Section: Benefits Risks and Implicationsmentioning
confidence: 99%
See 3 more Smart Citations